Synthesis, Structure, and Magnetic Properties of a Family of Complexes Containing a CoII2DyIII Pivalate Core and a Pentanuclear CoII4DyIII Derivative. Issue 12 (2nd March 2018) - Kiskin, Mikhail; Zorina‐Tikhonova, Ekaterina; Kolotilov, Sergey; Goloveshkin, Alexander; Romanenko, Galina; Efimov, Nikolay; Eremenko, Igor
Abstract: Invited for the cover of this issue is research led by Mikhail Kiskin from the Russian Academy of Sciences, Moscow, Russian Federation, in collaboration with the National Academy of Sciences of Ukraine, Kiev, Ukraine. The cover image shows the synthesis, structure, and magnetic properties of a family of complexes containing a Co2 Dy trinuclear core. Abstract : It is interesting to study new polynuclear complexes with nontrivial magnetic properties, but it is more interesting to create more complex architectures based on them… Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by M. Kiskin et al.